Problems of organization and activities of guerrillas of Ukraine during the summer of 1941-1942 from the point of view of the modern western historiography - Prylutska, Ludmila (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2021)
The article analyzes the peculiarities of western scientists’ coverage of the problems of organization and effectiveness of the guerrilla movement in Ukraine, which, in their opinion, had a rather complex and ambiguous phenomenon. The role of various factors that took place in the creation and leadership of the detachments, including both the factor of upper leadership of the movement, and the factor of spontaneity, has been examined. The circumstances that served as an accelerator for its expansion in 1943 have been clarified; the thesis of the "nationwide struggle against the Nazi invaders", to which western scientists have always been skeptical, has been considered from a critical point of view. There are some contradictions in the works of historians of Western Europe, the United States, Canada and other countries to the estimation of the effectiveness of guerrilla action. The authors did not ignore the typical problems associated with the attitude of Soviet leaders to the seemingly excessive independence of the guerrillas. Western historians also clarify the relationship between the guerrillas and the local community, which has not always been cloudless. In addition, they constantly emphasize the indifference of guerrilla leaders to the events of Holocaust. Moreover, as a rule, partisans of Jewish origin often felt protected from anti-Semitic manifestations only in mono-ethnic Jewish detachments. The situation of girls and women guerrillas was rather difficult; many of them were forced to become mistresses of certain captains due to the aggressive behavior of male guerrillas. It should be highlighted that the classic work of D.A. Armstrong (1922-2010), Professor of the University of Wisconsin, "Soviet guerrillas. Legend and Reality, 1941-1944” stated that by the autumn of 1942 there were almost no guerrillas in Ukraine. The exceptions were the regions of Sumy and Chernihiv; according to his estimates, even at the beginning of 1943 there were no more than 20,000 guerrillas in Ukraine. It is noteworthy that the historical department of the US Army during the Cold War was monitoring closely the Soviet publications on the activities of Soviet guerrillas. In 1965 the bibliography of books, essays, memoirs, and collections of documents on the guerrillas group in the occupied territory of the USSR, which was collected there, figured up to 227 titles.  Western scientists supported the formula of the "involuntary Resistance Movement" that existed in the occupied lands not only in Ukraine. According to them, the activities of the guerrillas had more psychological and political significance than purely military one - that is, the population should have felt that they were the representatives of the Soviet government.